The personal is pedagogical (?): Personal narratives and embodiment as teaching strategies in higher education - Frizelle, K.L. (South African Journal of Higher Education, 2020)
This article is a piece of “self-reflexive action work”. In it, I critically explore the pedagogical value of infusing my personal narrative and embodiment as a queer person into the content of a series of lectures on sexuality and gender. In an academic culture that promotes objectivity, incorporating one’s personal narrative and embodiment into the learning space as an educator is often criticised for being excessive and disruptive. I argue that if approached strategically and with an ethic of care, infusing personal stories and embodiment into educational content is pedagogically performative with the potential to challenge dominant cultural ideologies like heteronormativity. I use autoethnographic memory work, reflections from my teaching diary and theoretical insights from various critical theorist and pedagogues to make an argument for a queer, dialogical performative pedagogy that contributes towards the possibility of students who are able to think critically about their own gendered positions and relations within a wider context of heteronormativity.